Adding English : a guide to teaching in multilingual classrooms - Coelho, Elizabeth, 1946-; Rivers, Dyanne (Ontario : Pippin, 2004)
A comprehensive source of ideas and advice for enhancing the learning of all students in all subject areas and at all grade levels.
A welcoming environment -- How English works -- The language learning environment -- Language learning across the curriculum -- Afterword : a great adventure.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching as a second language; Linguistic minorities -- Education; Multicultural education